PENGARUH KUALITAS PRODUK, LOKASI, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI WARUNK UPNORMAL KEMANG PRATAMA - Muhammad Arsyla Rifkifadillah; Ricky Talumantak (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This study aims to determine and analyze product quality, location, and price perceptions of purchasing decisions at Warunk Upnormal Kemang Pratama Bekasi with a quantitative method. The data used is primary data by collecting questionnaire data by processing data using the Statistical Program for Social Science Version 20 application to obtain the research population, which are all consumers who come to Warunk Upnormal Kemang Pratama Bekasi. Samples were taken as many as 100 respondents using the Accidental Sampling technique. This research also uses multiple linear regression analysis. The technique used to calculate the data is a classiﬁed assumption test such as the data normality test, heteroscedasticity test, and multicollinearity test. There is also a data hypothesis using the F-Test and T-Test calculations. So, the results of this study state that these three variables, namely product quality, location, and price perception, partially have a significant positive effect on purchasing decisions at Warunk Upnormal Kemang Pratama. While the variables of product quality, location and price perception simultaneously affect purchasing decisions.